Evaluation of the genotoxic and transformation potential induced by asbestos compared to cleavage fragments - Sebastiano La Maestra; Gaia M. Militello; Stefano Alberti; Mirko Benvenuti; Laura Gaggero (Scientific Reports)
Abstract The World Health Organization has confirmed that asbestos fibres are carcinogenic, claiming that asbestos-related diseases should be eradicated worldwide. Actinolite, amosite, anthophyllite, chrysotile, crocidolite, and tremolite are regulated asbestiform mineral phases. However, in nature, asbestos minerals occur either in a fibrous and asbestiform (original morphology characterized by high length-to-width ratio and provided of high tensile strength and flexibility) or fibrous but not asbestiform appearance. This study used human epithelial cancer cells (A549) and a mouse fibroblast cell line (Balb/c 3T3) to compare the genotoxic and carcinogenic effects of a sample of amphibole asbestos with samples of fibrous not asbestiform named cleavage fragments (CV) obtained by grinding non-asbestiform amphiboles. The results showed that exposure of alveolar lung cells to asbestos and elongated mineral particles, in the habit of cleavage fragments (CF) derived from the grinding of non-asbestiform amphiboles and serpentines, causes cytotoxic effects, oxidative stress and genotoxic damage. Moreover, CF obtained from an actinolite schist induces a transformation effect in the Balb/c 3T3 model. Together, these findings highlight the importance of considering CF as a potential threat to human health since it can cause genotoxic damage by triggering cellular transformation processes that overlap with the mechanisms involved in the carcinogenesis processes of asbestos.